Análise de paternidade em policruzamentos e divergência genética de spondias tuberosa arruda com base em locos microssatélites - Santos, Viviane Nunes dos (2020)
The use of molecular markers in agriculture allowed great advances in genetic studies and, consequently, the improvement of plants. Umbuzeiro is still in the pre-breeding phase and many molecular techniques are little used. The objective of this work was to develop, transfer and adjust reactions with microsatellite markers for studies of population genetics and support in breeding activities in umbuzeiro. 14 microsatellite loci for umbuzeiro were developed, the transferability of another 15 loci of Spondias radlkoferi was evaluated and six species-specific were evaluated in eight crossroads. Of the 14 pairs of primers designed, six amplified, and only two showed polymorphism. All SSR loci of S. radlkoferi were transferred to umbuzeiro, however, only four were polymorphic. Among the six species-specific SSR loci, all showed good resolution in gels. In total, 12 SSR loci were identified, with content of information polymorphism ranging from 0.195 to 0.744 and expected and observed heterozygosity from 0.233 to 0.825 and 0.250 to 0.750, respectively, being indicated for studies of population genetics and species improvement. The microsatellite loci allowed to identify 85% of the male parents of the progenies of BGU30 and 32% of the progenies of BGU37, indicating that cross-breeding is an alternative for obtaining hybrids in umbuzeiro. Progenies were obtained resulting from the crossing of BGUs 68, 44 and 48 with BGU 30, unprecedented and of great interest for the improvement of the species. The similarity coefficient between the 24 accessions varied from 0.30 to 0.84, indicating a great divergence between the accessions. The Bayesian analysis suggests two subpopulations, one formed by the Januária region and the other by the Juazeiro, Uauá and Petrolina regions. The FST value of 0.12 in the molecular analysis of variance indicates moderate genetic differentiation between populations, suggesting that the genetic variability of umbuzeiro populations is moderately structured according to origin. The analyzes indicate that the umbuzeiro's genetic diversity is not evenly distributed in the studied regions, being recommended the collection of germplasm from a larger number of populations to increase the genetic diversity of the species.